РОЛЬ НАЦИОНАЛЬНОЙ ИДЕИ И НАЦИОНАЛЬНОЙ КУЛЬТУРЫ В ПОСТРОЕНИИ ПРАВОВОГО И ДЕМОКРАТИЧЕСКОГО ГОСУДАРСТВА И КОНСОЛИДАЦИИ КАЗАХСТАНСКОГО ОБЩЕСТВА - Pralieva, G.K. (Journal of actual problems of jurisprudence, 2019)
At modern period of the building legal democratic state and consolidation kazakhstan society special place occupies the national idea in national politician and national and spiritual culture kazakhstan society.